Prioritizing among Equals. Only Medical Criteria? Why Medical Criteria Are Not Always The Trump Card - Semplici, Stefano (Filosofia Morale/Moral Philosophy, 2022)
The COVID-19 pandemic has raised two critical issues in terms of prioritization. Its breakout was accompanied by images of emergency rooms flooded by patients. Vaccines are for prevention, which is something other than treating a disease. In a first phase, however, they too were a scarce resource. In both cases, the elderly, which were much more at risk of hospitalization and death, were at the forefront of the challenge that healthcare professionals and public opinion were confronted with. With regard to ventilators, that risk appeared to go hand in hand with that of being discriminated against. With vaccines, the special vulnerability of the elderly imposed itself as an unquestioned reason for priority. Are medical (clinical) criteria the only ones to be considered in a normative perspective? In the case of COVID-19, it was perhaps easier to focus on them because of the characteristics of the pandemic. Had they been different, some choices would have been more difficult to make.